Provenance of the Highland Border Complex: constraints on Laurentian marginaccretion in the Scottish Caledonides - Cawood, P; Merle, Renaud; Strachan, R; Tanner, P (Geological Society of London, 2012)
Contrasting tectonic models for the Highland Border Complex in the Scottish Caledonides view it either as part of the rifted Laurentian margin of the Iapetus Ocean or as an oceanic terrane. Detrital zircon data from sandstones of the complex yield age peaks at 2.8–2.6, 1.3 and 1.1–1.0 Ga and minor peaks at c. 1.7–1.9 Ga. These characteristics compare closely with those of the upper Dalradian Supergroup of the adjacent Grampian terrane, and with the record of eastern Laurentia. The data are also consistent with the Laurentian provenance indicated by palaeontological evidence from the complex, and field evidence for continuity with the Dalradian Supergroup. Detrital ages for the Cambrian Salterella Grit of the Caledonian foreland compare with those for approximately age-equivalent sandstones from the Highland Border Complex. Both were contemporaneous with the regressive Hawke Bay event, accounting for similarities in provenance, and further linking the Highland Border Complex to Laurentia. The Grampian terrane was being uplifted and shedding detritus throughout the Ordovician and Silurian. The absence of this event from the detrital zircon records of either the Midland Valley or Southern Upland terranes suggests that these blocks cannot have been in their current location relative to the Grampian terrane before the end of the Silurian.